2020
DOI: 10.1590/1518-8345.3520.3308
|View full text |Cite
|
Sign up to set email alerts
|

Care opportunities for premature infants: home visits and telephone support

Abstract: Objective: to analyze opportunities for orientations to promote the care of premature infants during home visits and telephone support. Method: a qualitative study from the perspective of philosophical hermeneutics conducted with 18 mothers of premature infants discharged from hospital. Hospital contact and interviews were carried out, 15 and 45 days after discharge and at the infants’ six months of life, with data analysis by interpretation of meanings from 25 home visits and 56 telephone support co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
13

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(49 citation statements)
references
References 27 publications
0
19
0
13
Order By: Relevance
“…Furthermore, many mothers expressed concerns about keeping to their infants' feeding schedule, as well as waking up to regularly check their infant's breathing status. Maternal concerns about feeding their preterm infant at home are found in similar studies (Da Silva et al 2020).…”
Section: Subtheme 22: Parental Perception Of Childhood Vulnerability Was Also Heavily Influenced By Medical Interventionsmentioning
confidence: 60%
“…Furthermore, many mothers expressed concerns about keeping to their infants' feeding schedule, as well as waking up to regularly check their infant's breathing status. Maternal concerns about feeding their preterm infant at home are found in similar studies (Da Silva et al 2020).…”
Section: Subtheme 22: Parental Perception Of Childhood Vulnerability Was Also Heavily Influenced By Medical Interventionsmentioning
confidence: 60%
“…Ademais, o acompanhamento por meio telefônico favorece a apreensão de necessidades de saúde e esclarecimento de dúvidas das mães acerca dos cuidados básicos e cotidianos à criança 28 , conforme evidenciou uma das participantes do estudo, ao mencionar que o acompanhamento e a continuidade do cuidado por telefone foram capazes de solucionar problemas de saúde dos seus filhos.…”
Section: Discussionunclassified
“…It has been identified that strategies involving the use of information and communication technologies are useful in this purpose. ( 12 ) Furthermore, it has been documented that telephone support can help to solve their concerns in the process( 13 ) and, with such, becomes an opportunity to strengthen preparation processes for the discharge.…”
Section: Discussionmentioning
confidence: 99%